Meningkatkan Minat Belajar Siswa Kelas X Program Keahlian Teknik Komputer Jaringan pada Pembelajaran Sistem Komputer dengan Pendekatan Open-Ended - Wulandari, Wiwin Dyah (FKIP Unirow Tuban, 2022)
In an effort to overcome the problem of low interest in learning for class X TKJ SMK Negeri 1 Tuban students in computer systems subjects, the author applies an Open-Ended Problem-Based approach (Open Problem) in the even semester of the 2017/2018 school year. In the first cycle, after implementing the Problem-Based Open-Ended approach, there were 3 students whose interest in learning was very high. In the High category, there are 8 students. In the medium category, there are 20 students. In the Low category, there are 4 students. Meanwhile, for the very low category, there were no students with this learning interest category. In cycle II, after making improvements based on the results of reflection in cycle I, on the implementation of learning with an Open-Ended Problem-Based approach, the increase in learning interest of class X TKJ students became more maximal. In this second cycle, there were 8 students whose interest in learning was classified as very high, this number increased when compared to the first cycle stage which there were only 3 students. In the High category, there were 20 students, this number increased when compared to cycle 1 where there were only 8 students. In the Medium category, there were 8 students, this number decreased when compared to the first cycle which reached 21 students. The decrease in the Medium category is interpreted as positive, because initially 21 students who only got the Medium category, experienced an increase to get the High category of learning interest. In this second cycle, there were no students who got the Low and Very Low categories. The decrease in the number of students in the Low and Very Low categories until it reaches 0 (None), this shows that students' interest in learning really has increased after the implementation of learning using the Problem-Based Open-Ended approach in this second cycle.